Field of view and voxel size considerations in cone-beam computed tomography: a systematic review - Syahraini, Syurri Innaddinna; Kiswanjaya, Bramma; Priaminiarti, Menik; Bachtiar-Iskandar, Hanna H (Odonto : Dental Journal, 2024)
Background: Several factors must be considered when selecting the appropriate field of view (FOV) and voxel size for good image quality on Cone Beam Computed-Tomography (CBCT). The purpose of this study is to determine the factors that must be considered in selecting the appropriate FOV and voxel size to achieve good image quality according to the purpose of the examination. Method: Articles in Q1 and Q2 journals published within the period from January 2016 to September 2021 were searched from Scopus and PubMed online using the keywords field of view/FOV in CBCT, voxel size in CBCT, and FOV and voxel size in CBCT. On the basis of the article selection criteria, 13 journals were included in the study. Also included in the study were several types of three-dimensional (3D) CBCT machines: Planmeca ProMaxÂ® 3D ProFaceTM, i-Cat Cone Beam 3D, Picasso Trio CBCT: Carestream unitÂ® CS 9300 CBCT, and Accuitomo F17D 3D CBCT. Result: It is generally recommended that a 0.2 mm voxel size be used to detect periodontal disease, secondary caries, fractures, external resorption, and endodontic complications. Meanwhile, for root fractures with an intracanal metallic post and an anatomic isthmus in the root canal, a 0.1 mm voxel size is recommended to be used, and for evaluating the implant, 0.3 mm and 0.4 mm voxel sizes are recommended. Conclusion: It was found in the review that most of the selected studies recommended using the smallest FOV available in the CBCT unit to detect pathological conditions and important anatomical structures.